Industrial Melanism in the Peppered Moth Is Not Associated with Genetic Variation in Canonical Melanisation Gene Candidates - van't Hof, Arjen E. (Public Library of Science, 2010)
Industrial melanism in the peppered moth (Biston betularia) is an iconic case study of ecological genetics but the molecular identity of the gene determining the difference between the typical and melanic (carbonaria) morphs is entirely unknown. We applied the candidate gene approach to look for associations between genetic polymorphisms within sixteen a priori melanisation gene candidates and the carbonaria morph. The genes were isolated and sequence characterised in B. betularia using degenerate PCR and from whole-transcriptome sequence. The list of candidates contains all the genes previously implicated in melanisation pattern differences in other insects, including aaNAT, DOPA-decarboxylase, ebony, tan, tyrosine hydroxylase, yellow and yellow2 (yellow-fa). Co-segregation of candidate gene alleles and carbonaria morph was tested in 73 offspring of a carbonaria male-typical female backcross. Surprisingly, none of the sixteen candidate genes was in close linkage with the locus controlling the carbonaria-typical polymorphism. Our study demonstrates that the ‘carbonaria gene’ is not a structural variant of a canonical melanisation pathway gene, neither is it a cis-regulatory element of these enzyme-coding genes. The implication is either that we have failed to characterize an unknown enzyme-coding gene in the melanisation pathway, or more likely, that the ‘carbonaria gene’ is a higher level trans-acting factor which regulates the spatial expression of one or more of the melanisation candidates in this study to alter the pattern of melanin production.